Terapia fotodinâmica como coadjuvante no processo de cicatrização do pé diabético: série de casos - Ferreira, Rita de Cássia (2022)
Diabetic foot is one of the main complications of diabetes mellitus with high mortality, morbidity and large use of public resources in long clinical and surgical treatments. The treatment of these lesions is challenging due to their multifactorial etiology. This study aimed to evaluate the clinical evolution of patients with diabetic foot treated with photodynamic therapy using the Bates-Jensen (BJ) scale. Twenty-one patients from the vascular surgery clinic of the Conjunto Hospitalar do Mandaqui in the city of São Paulo were followed up, 16 men and 5 women, with a mean age of 58 years. Patients underwent standard institutional care plus antimicrobial Photodynamic Therapy (aPDT) using a 0.01% methylene blue photosensitizer and laser irradiation (660 nm, 100 mW, 1W/cm2, 60 J/cm2, 6J per point). The primary dressing used as a dressing was hydrofiber with silver applied after PDT. The BJ scale was used before and after the end of PDT to assess the evolution of the lesions, as well as the area, characteristics of the tissue bed, characteristics and amount of exudate, perilesional edema, granulation tissue and epithelialization. Patients were divided into 4 groups (discharged, discharged due to worsening, in treatment and loss) that were compared using the SPSS Statistics software with a significance of 0.05. The results showed that in the total sample there was a significant difference in the values of the BJ scale before and after aPDT. Regarding the BJ items evaluated after aPDT in the general sample, no significance was found in the size of the lesion, but there was significance in the detachment, amount and type of necrotic tissue and perilesional hardening. When evaluating these same BJ items in patients who were discharged, there was a statistical difference in lesion size, type and amount of necrotic tissue, type and amount of exudate and perilesional edema. In this follow-up, aPDT proved to be an effective, safe, low-cost, well-tolerated treatment, with high patient adherence and feasibility of implementation in the public health service.